PEMBUATAN ANTI DROPLED BOARD BAGI PEDAGANG PASAR MENYAMBUT NEW NORMAL WABAH COVID 19 - Amrozi Khamidi; Karwanto Karwanto; Nunuk Hariyati (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2021)
Facing the new normal era of the Covid 19 outbreak, people are returning to activities like before the Covid 19 outbreak, amid the transmission of the Covid outbreak which is still quite high, all people are required to be able to maintain distance and transmission of firus covid 19 through dropled. For people who work in traditional market markets who are susceptible to contracting the Covid 19 virus, they need an anti-dropled board insulation tool so that dropled splashes are blocked. The goal is to find a solution to prevent the spread of the corona / Covid virus 19 Making anti-dropled boards for market traders to welcome the new normal 19 outbreak. The results of this PKM goal are according to the target, namely preventing the COVID-19 pandemic. In response to the new normal by maintaining vigilance against the transmission of covid, all caution must be done, especially traditional market traders, to prevent the spread of the Covid 19 virus through droplets, it is necessary to make special tools Virus prevention through these droplets is called a thick PVC plastic insulator / anti-dropled board combined with a lightweight iron frame so that communication between traders and buyers does not occur but is blocked by the tool.